Characterization of muscarinic and P2X receptors in the urothelium and detrusor muscle of the rat bladder - Masaki Ogoda; Yoshihiko Ito; Yusuke Fuchihata; Satomi Onoue; Shizuo Yamada (Elsevier, 2016)
Muscarinic and purinergic (P2X) receptors play critical roles in bladder urothelium under physiological and pathological conditions. Aim of present study was to characterize these receptors in rat bladder urothelium and detrusor muscle using selective radioligands of [N-methyl-3H]scopolamine methyl chloride ([3H]NMS) and αβ-methylene ATP [2,8-3H]tetrasodium salt ([3H]αβ-MeATP). Similar binding parameters for each radioligand were observed in urothelium and detrusor muscle. Pretreatment with N-(2-chloroethyl)-4-piperidinyl diphenylacetate (4-DAMP mustard) mustard revealed co-existence of M2 and M3 receptors, with the number of M2 receptors being larger in the urothelium and detrusor muscle. Intravesical administration of imidafenacin and Dpr-P-4 (N → O) (active metabolite of propiverine) displayed significant binding of muscarinic receptors in the urothelium and detrusor muscle. The treatment with cyclophosphamide (CYP) or resiniferatoxin (RTX) resulted in a significant decrease in maximal number of binding sites (Bmax) for [3H]NMS and/or [3H]αβ-MeATP in the urothelium and detrusor muscle. These results demonstrated that 1) pharmacological characteristics of muscarinic and P2X receptors in rat bladder urothelium were similar to those in the detrusor muscle, 2) that densities of these receptors were significantly altered by pretreatments with CYP and RTX, and 3) that these receptors may be pharmacologically affected by imidafenacin and Dpr-P-4 (N → O) which are excreted in the urine.